PENGEMBANGAN BAHAN AJAR TARI DANA SYARAH UNTUK SMP KELAS VIII MENGGUNAKAN MODEL PEMBELAJARAN SIMULASI - Gusmiyeni, Gusmiyeni; Sudaryono, Sudaryono; Karim, Maizar (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2013)
This research aim to describe the development process by equiping procedure and conditions and also attractive and efective teaching materials implementation (and book of DVD penyerta) artistic of dance Dana Syarah use Model Study of supported by Simulation is theorys learn behavioral and of konstruktivisme.The development model is used by adapting the Model of Borg &Gall(2003) and modified into six steps. The result of development validation as a whole can be seen by its detail as follows 1) media device expert give criterion very do well by yielded product desain 2) items expert give criterion do well by materials book items content teach along with DVD penyerta 3) coleage give used competent criterion for the process of study of dance art, and 4) student alone and group give respon that easy and very attractive teaching materials product to be studied.The implication of this research, study can be done/conducted by student alone and or group, where and whenever can be executed. To instructor in other school of materials teach this become example and become inspiration to make other teaching materials product. Keyword: teaching materials, art of Dana Syarah dance, simulation of model.